THE EIGENVALUE PROBLEMS FOR DIFFERENTIAL PENCILS ON THE HALF LINE - Neamaty, A.; Khalili, Y. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2012)
In this paper we study the solution of the boundary value problem for second-order differential operator on the half-line having jump point in an interior point. Using of the fundamental system of solutions, we investigate the asymptotic distribution of eigenvalues.